Language learning, gender and desire Japanese women on the move - Takahashi, Kimie (Critical language and literacy studies, 2013)
This book explores Japanese women's desire for English as a means of identity transformation and as access to the West and its masculinity. Drawing on ethnographic data and critical discourse analysis, the book illuminates how such desire impacts upon the linguistic, social, and romantic choices made by young women in Japan and overseas.